IoT-based instrumentation development for reaction time, kick impact force, and flexibility index measurement - Ng, Chun Keat; Jumadi, Nur Anida (2022)
This paper presents an Internet of Thing (IoT)- based instrumentation development using vibration sensor, force sensor, and Blynk app to obtain the reaction time, kick impact force, and flexibility index based on visual stimulants. Besides the Blynk app, vibration, and force sensors, other main components of the prototype are the Arduino NodeMCU microcontroller, and three LEDs (yellow, red, and green). The developed prototype was able to record the reaction time, kick impact force, and flexibility index. These outputs could be viewed not only on the Organic Light Emitting Diode (OLED) display but also on the smartphone via the Blynk app interface. To evaluate the performance of the developed prototype, four male Silat athletes weighing between 61kg to 80kg were recruited for this experiment. They were requested to undergo a Simple Reaction Time (SRT) task which requires them to perform three trials of the front kick. From the SRT findings, it can be deduced that 75% of the participants reacted faster towards green LED with the fastest reaction time recorded was 1485.2±126.7ms compared to yellow and red LEDs. In the future, the design of the hardware in terms of circuitry and hardware casing will be improved for a better prototype presentation. Secondly, a big sample size of subjects and different branches of combat sports will be recruited to assist in further analysis. Furthermore, the sound stimuli will be included in future studies. Lastly, further research should be conducted to assess the effect of colored stimuli on the reaction time of the athletes.